(untitled) (Faculty of Education Scientific Journal, 2024)
The study aimed to identify on the most important obstacles to sustainable agriculture development from point of view officials and specialists in the agricultural sector in the sirte city.The researcher used the descriptive analytical method considering the appropriate for this study ,the questionnaire tool was used as a means of collecting data about the subject of the study ,the sample was distributed to officials and specialists in the agricultural sector in the sirte city ,numbering 86 and thy were selected using the stratified random sampling method ،the group study continued to produce results , the most important of which was the problem of delay in decision making and thus delay in the arrival of found allocated to agriculture sector ,weak a commitment to policy implementation and programs in the field of agricultural .This led to a decline in the production rate of agricultural crops which resulted in a weakness in a sustainable agricultural development ,the study recommended that there should be role for the state in addressing obstacles to agricultural development due to weak financial and technological capabilities of the private agricultural sector on the one hand and complexity of agricultural development problems in the Libya on the others hand